EXAMINING TEACHERS’ READINESS TO IMPLEMENT THE KURIKULUM MERDEKA IN THE MADRASAH IBTIDAIYAH CONTEXT - Priatmoko, Sigit; Santoso, Anang; Dewi, Radeni Sukma Indra; Sugiri, Wiku Aji (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2024)
The Indonesian government continues improving teachers’ readiness to implement the Kurikulum Merdeka. Teacher readiness plays an important role in supporting the implementation of the Kurikulum Merdeka. This study aims to examine teachers’ readiness to implement the Kurikulum Merdeka. This study used a descriptive quantitative approach. Data was mainly collected by distributing online questionnaires through the Whatsapp chat application. The questionnaire was used to collect data on teacher readiness in (1) understanding of The Kurikulum Merdeka policies, (2) understanding of curriculum structure, (3) understanding of the Pancasila Student Profile Strengthening Project (P5), (4) readiness to develop lesson plans, (5) readiness to deliver instruction, and (6) readiness to conduct instructional assessments. Forty Madrasah Ibtidaiyah (MI) teachers were involved as respondents. They were in-service teachers who were students of the Teacher Professional Education Study Program (PPG). They came from the provinces of East Java, South Sulawesi, West Nusa Tenggara, Southeast Sulawesi, West Java, South Kalimantan, East Nusa Tenggara, and Bali. The data were analyzed using the quantitative descriptive method. The results showed that measuring the six key aspects of the Kurikulum Merdeka showed that teacher readiness was in the high category. However, some respondents still get a medium score in learning and assessment. So, the research respondents are sufficiently ready to implement the Kurikulum Merdeka but still need to improve their readiness for learning and assessment.